2007
DOI: 10.1016/j.rcl.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Issues to Consider in Converting to Digital Mammography

Abstract: This article outlines the reasons that many radiology practices are converting to digital mammography. In addition, it provides basic information about the issues that must be considered in making the transformation. These issues include technical matters regarding image display, storage, and retrieval as well as clinical and ergonomic considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Each manufacturer provides one or more choices of radiologist review workstation, and the FDA has approved at least six additional third-party review workstations for interpretation of digital mammograms. One might assume, as we did, that because these acquisition and display systems are DICOM compliant and FDA approved, lesion size measurements would be accurate and consistent regardless of the acquisition-display combination [1]. Through first-hand experience, we have learned that this is not always the case.…”
Section: Methodsmentioning
confidence: 83%
“…Each manufacturer provides one or more choices of radiologist review workstation, and the FDA has approved at least six additional third-party review workstations for interpretation of digital mammograms. One might assume, as we did, that because these acquisition and display systems are DICOM compliant and FDA approved, lesion size measurements would be accurate and consistent regardless of the acquisition-display combination [1]. Through first-hand experience, we have learned that this is not always the case.…”
Section: Methodsmentioning
confidence: 83%
“…Furthermore, these studies included independent double readings of digital mammograms (17,24), and for the study that found a significantly higher rate (24) there was, on average, an 8-year difference between study periods of the SFM and CR cohorts. The Digital Mammographic Imaging Screening Trial, or DMIST, examined performance by machine type as an exploratory analysis and found that the CR machine used (Fuji CR) was equivalent to SFM in cancer detection and positive predictive value; however, the sample size was much smaller and the investigators did not adjust for patient or center characteristics (33). The ability to depict small structures in DM depends on the spatial resolution, which in turn depends on the size of the detector element (pixel size) and scattering of light in the detector.…”
Section: Breast Imaging: Digital Versus Screen-film Mammography In Comentioning
confidence: 99%
“…5 FFDM systems were used in this paired multicentre screening trial, which enrolled 49 528 females. One of these was a CR system, which contributed 8957 (21%) of the total 42 760 evaluable cases and detected 17.9% of the cancers [26]. The overall sensitivity and specificity for cancer detection of CR and DR systems has been shown to be similar in other largescale studies and as good as or better than SFM [29,30].…”
Section: Discussionmentioning
confidence: 88%
“…Although there are many clinical studies comparing the performance of 9,[18][19][20][21][22][23][24][25][26], there are fewer that compare CR with SFM or DR [8,25,[27][28][29][30][31][32]. We sought a method to compare the clinical diagnostic quality of two types of CR technology with that of SFM.…”
mentioning
confidence: 99%